2014
DOI: 10.1590/s0102-8650201400150008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liver regeneration with use of diet supplemented with l-arginine

Abstract: PURPOSE:To compare controlled liver regeneration in rats submitted to 60% hepatic resection having L-arginine supplemented diet, based on weight changes of the regenerated liver, laboratory parameters of liver function and pathological findings. METHODS:Thirty-six rats were divided into two groups, control and L-arginine. The first received standard chow and saline solution by gavage. The second had supplementation with L-arginine. Animals were killed on postoperative period at 24h, 72h and seven days.For anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Enteral immunonutrition with arginine reduces the risk of infections in patients submitted to major operations [80]. The supplementation with L-arginine diet in rats hepatectomized was unable to confirm benefits in liver regeneration [65]. Conversely, a similar study using supplementation of L-glutamine in the diet of rats after PH revealed an increase in the amount of albumin and beneficial effects for liver regeneration [66].…”
Section: Fatty Acids Arginine and Nucleotidesmentioning
confidence: 99%
“…Enteral immunonutrition with arginine reduces the risk of infections in patients submitted to major operations [80]. The supplementation with L-arginine diet in rats hepatectomized was unable to confirm benefits in liver regeneration [65]. Conversely, a similar study using supplementation of L-glutamine in the diet of rats after PH revealed an increase in the amount of albumin and beneficial effects for liver regeneration [66].…”
Section: Fatty Acids Arginine and Nucleotidesmentioning
confidence: 99%
“…Evidence from both human and animal studies has indicated that preoperative supplementation with branched-chain amino acids (BCAA) positively impacts the volume increase and hepatic regeneration after partial hepatectomy. 16,17 In a review published in 2005 by Singer et al, 15 the authors endorse donor nutrition as a therapeutic intervention to modulate IRI and safeguard the functionality of the graft after the harvesting procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from both human and animal studies has indicated that preoperative supplementation with branched‐chain amino acids (BCAA) positively impacts the volume increase and hepatic regeneration after partial hepatectomy 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…[ 55 ] It is observed that L-Arginine could improve the liver proliferation and elevate ALP in the rats underwent partial hepatectomy and the increase in the ALP level is considered as a liver cell regeneration index. [ 56 ] Therefore, it seems that increased ALP induced by L-Arginine is not associated with liver damage. Ischemia-induced BW loss and L-Arginine treatment enhanced the enzyme level.…”
Section: Discussionmentioning
confidence: 99%